New genes often acquire male-specific functions but rarely become essential in Drosophila - Kondo, Shu (Genes Dev, 2017)
Relatively little is known about the in vivo functions of newly emerging genes, especially in metazoans. Although prior RNAi studies reported prevalent lethality among young gene knockdowns, our phylogenomic analyses reveal that young Drosophila genes are frequently restricted to the nonessential male reproductive system. We performed large-scale CRISPR/Cas9 mutagenesis of “conserved, essential” and “young, RNAi-lethal” genes and broadly confirmed the lethality of the former but the viability of the latter. Nevertheless, certain young gene mutants exhibit defective spermatogenesis and/or male sterility. Moreover, we detected widespread signatures of positive selection on young male-biased genes. Thus, young genes have a preferential impact on male reproductive system function.